Carbohydrates and cancer: an overview of the epidemiological evidence. - Key, T; Spencer, E (2007)
OBJECTIVE: To assess the epidemiological evidence on dietary carbohydrates and the risk of developing cancer. METHOD: Review of published studies, concentrating on recent systematic reviews, meta-analyses and large prospective studies. CONCLUSIONS: Carbohydrates have not been intensively investigated in epidemiological studies of diet and cancer. There is a moderately large amount of data on the possible association between dietary fibre and the risk for colorectal cancer; the results of studies have varied and no firm conclusion can be drawn, but the available data suggest that high intakes of dietary fibre possibly reduce the risk for colorectal cancer. There are also limited data which suggest that high intakes of sucrose might increase the risk for colorectal cancer and that high intakes of lactose might increase the risk for ovarian cancer. For other components of carbohydrates and other types of cancer, the available data are too sparse to draw even tentative conclusions. Further research is needed on the possible associations of carbohydrates with cancer risk.